2013
DOI: 10.1371/journal.pone.0058371
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Reduces Infarct Size and Preserves Cardiac Function in Rat Myocardial Ischemia/Reperfusion Injury through Activation of PI3K/Akt/Nrf2 Pathway

Abstract: BackgroundThe present study investigates the effects and mechanisms of α-Lipoic acid (LA) on myocardial infarct size, cardiac function and cardiomyocyte apoptosis in rat hearts subjected to in vivo myocardial ischemia/reperfusion (MI/R) injury.Methodology/Principal FindingsMale adult rats underwent 30 minutes of ischemia followed by 3, 24, or 72 h of reperfusion. Animals were pretreated with LA or vehicle before coronary artery ligation. The level of MI/R- induced LDH and CK release, infarct size, cardiomyocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 42 publications
5
102
1
1
Order By: Relevance
“…45,46) Activation of MAPKs or Akt is known to be involved in the upstream signaling pathway for the expression of HO-1 in neuronal and other cell types. 47,48) It has been reported that berberine, an alkaloid derived from Coptis chinensis, induces the stimulation of Akt and p38 MAPK, which is linked to HO-1 expression and neuroprotection in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…45,46) Activation of MAPKs or Akt is known to be involved in the upstream signaling pathway for the expression of HO-1 in neuronal and other cell types. 47,48) It has been reported that berberine, an alkaloid derived from Coptis chinensis, induces the stimulation of Akt and p38 MAPK, which is linked to HO-1 expression and neuroprotection in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under homeostatic conditions, NRF2 levels are also maintained at low levels due to E3 ubiquitin ligase-mediated ubiquitylation and proteasome-dependent degradation of NRF2 (14). Under ischemia-stress conditions, NRF2 degradation was markedly inhibited by high levels of oxidative stress in the liver, heart, kidney and brain (15)(16)(17)(18). Activation of NRF2 induces the expression of heme oxygenase-1 (HO-1), suggesting that NRF2 is essential for the regulation of HO-1.…”
Section: Introductionmentioning
confidence: 99%
“…In previous decades, using several different experimental models of I/R, studies have demonstrated the protective effects of LA against I/R-induced injury, including myocardial injury (7), peripheral nerve injury (8), testicular injury (9) and retinal injury (10). In addition, it has been reported that LA can activate phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt and extracellular signal-regulated kinase 1/2 (ERK1/2) pathways to induce protection against I/R injury in other organs (11)(12)(13) to the best of our knowledge, few studies were reported to address whether LA has neuroprotective effects against cerebral I/R-induced injury and its potential mechanisms. In the present study, the neuroprotective effects of LA in rats were investigated with 90 min middle cerebral artery occlusion (MCAO)/24 h reperfusion-induced injury.…”
Section: Introductionmentioning
confidence: 99%